Sensorless control in full speed domain of interior permanent magnet synchronous motor based on hybrid observer - Ying Jie Gao; Shu Jia Yan; Mei Song Tong; Jun You Chen; Qiang Chen (Scientific Reports, 2024)
Abstract Aiming at the problem that an Interior Permanent Magnet Synchronous Motor (IPMSM) cannot be smoothly started in zero-low speed range and smoothly transitioned to medium-high speed range by a single observer. This paper proposes a full-speed range control algorithm based on the fusion of pulsating high-frequency injection and back electromotive force (EMF) position error information. In the low-speed range or at start-up, a square-wave high-frequency signal is injected, and the obtained high-frequency current signal is processed to obtain the rotor position error information. The phase shift due to the introduction of a filter is reduced, which improves the control bandwidth and reduces the noise. To ensure smooth switching of the observer, the observer uses a dual second-order generalized integrator module to output the angular frequency in the low-speed range. A higher-order sliding mode observer based on an inverse EMF model obtains rotor position error information at high speeds. During switching, the rotor position information is processed by a fusion strategy, and the obtained hybrid information is fed into the system to improve the stability of the motor operation. A 0.2 kW IPMSM position sensorless vector control system verifies the algorithm’s accuracy.